FRI0511 Detection of Anti-Th/To Antibodies in Patients with Various Rheumatic Diseases and their Clinical Features. (10th June 2014) - Hosono, Y.; Nakashima, R.; Imura, Y.; Yukawa, N.; Yoshifuji, H.; Ohmura, K.; Mimori, T.
Abstract : Background: Anti-Th/To were initially reported to be specific for SSc or Raynaud's disease with a short duration. Clinically, anti-Th/To were associated with features like puffy fingers, hypothyroidism and a significantly lower frequency of arthritis. But previous studies were limited in patients with SSc and the relatively low number of anti-Th/To positive patients. Therefore, whether anti-Th/To were also detected in other rheumatic diseases and their clinical significance remained unclear. Objectives: We intended to evaluate the presence and clinical relevance of the patients with anti-Th/To in various connective diseases (CTDs) including undifferentiated arthritis and to clarify these clinical features for improving appropriate medical intervention. Methods: Clinical data and serum samples were collected from adult Japanese patients with various CTDs who had been admitted to our department from January 2005 to December 2013. Anti-Th/To Abs were screened using the RNA immunoprecipitation assay and determined as positive if 7-2 and 8-2 RNA were immunoprecipitated. Patients with UA were defined as those who had arthritis in one or more joint at the first visit and not diagnosed after followed more than 1 year. Results: 50 patients (40 females and 10 males) were positive for anti-Th/To. The average age was 51.9±16.9 years old. 11 (22%) were detected scleroderma (SSc). Interestingly, 9 (18%) UA patients without sclerodactyly were detected along with 9 (18%) RA. 5 (10%) interstitial pneumonia, 4 (8%) Raynaud's disease, 3 (6%) myositis, 2 (4%) SLE, 2 (4%) erythroderma, and each one with MCTD, pleural effusion, diarrhea, Sjögren's syndrome and miscarriage. There were no significant differences in age of onset, sex, type of antinuclear Ab, the presence of morning stiffness between each group. More than half of patients (52%, 26/50) with anti-Th/To had arthritis. In those patients, 9 (35%) were diagnosed as RA, and 8 (31%) were other CTDs. But 9 (35%) remained UA after more than 1 year. The positive rates of RF and ACPA in RA group were higher than in UA group (89% vs 11%, P<0.05 and 56% vs 0%, P<0.05). All patients in RA group received treatment with disease-modifying anti-rheumatic drugs including biologics, whereas only 22% (2/9) in UA group with only low dose of prednisolone (P<0.05). There was a tendency that UA group had more frequent Raynaud's phenomenon compared with RA group (44% vs 11%, 0.05<P). No one with Raynaud's phenomenon in UA group observed sclerodactyly, while all of SSc and 50% of SLE had. 50% of SLE and SSc groups were treated with vasodilators, though no patients with Raynaud's phenomenon in UA group were treated. One of UA group diagnosed as SSc after 2 years according to the appearance of sclerodactyly, but no medication was needed. Conclusions: Our study differed from previous studies in which anti-Th/To were specific for SSc, but also detected in patients with UA without sclerodactyly and other rheumatic diseases. In addition, more than half of patients with anti-Th/To had arthritis, and 35% of those patients were still undifferentiated after 1 year follow-up. Anti-Th/To Ab positive UA without sclerodactyly could be followed with no specific medication. In addition, the possibility that arthritis patients with anti-Th/To but without SSc may develop SSc later in the course of the disease was indicated. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3953